2020
DOI: 10.1038/s41598-020-68896-1
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative live-birth, perinatal and obstetric outcomes for POSEIDON groups after IVF/ICSI cycles: a single-center retrospective study

Abstract: Recently, perinatal outcomes and cumulative live birth rate (cLBR) have widely been utilized to assess the fertility outcomes and safety of assisted reproductive technology (ARt), but more robust research is needed to address the success rates of live-healthy births resulting from this procedure, particularly for patients with low prognosis. this study aims to assess and comparative perinatal outcomes and cLBR per cycle of in vitro fertilization/intracytoplasmic sperm injection (iVf/icSi) between four groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 43 publications
5
16
2
Order By: Relevance
“…As for women with predicted poor ovarian reserve, a recent retrospective analysis on 825 IVF cycles showed that the live birth rate decreased through Poseidon groups 1, 3, 2, and 4 in order ( 48 ). It implies that both AMH or AFC as well as age have an impact on the prediction of live birth.…”
Section: Initial Observationsmentioning
confidence: 99%
“…As for women with predicted poor ovarian reserve, a recent retrospective analysis on 825 IVF cycles showed that the live birth rate decreased through Poseidon groups 1, 3, 2, and 4 in order ( 48 ). It implies that both AMH or AFC as well as age have an impact on the prediction of live birth.…”
Section: Initial Observationsmentioning
confidence: 99%
“…Among different study designs, it is widely recognized that RCTs represent the optimal way to verify the clinical efficacy of specific interventions ( 59 , 60 ). In RCTs, participants are prospectively and randomly allocated to either intervention or another, following strict inclusion and exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 , 38 ] For better clinical decisions of these patents, POSEIDON criteria were carried out in 2016, [ 4 , 5 ] dividing low prognosis patients into 4 groups with their age, AMH, AFC, and retrieved oocytes number of previous cycle. Retrospective studies suggested significant differences on CPR and LBR among 4 groups [ 6 , 7 ] ; these results might be adequate references for building a predicting model in managing POR patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 , 5 ] With this classification, studies analyzed the results of completed IVF/ICSI cycles of POR patients, showing that in cumulative live birth rates (CLBR), optimistic outcomes were observed in group 1, 2, and 3. [ 6 , 7 ] Thus, POSEIDON criteria might provide a more detailed and precise model in predicting IVF/ICSI prognosis on POR women. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%